Critical Interculturality and Sociomuseology – decolonial practices and their intersections in Freire's praxis (Cadernos de Sociomuseologia, 2023)
Critical interculturality and sociomuseology break with power hierarchies and the dominant hegemonic status quo that operates in formal and non-formal educational institutions, based on the recognition of the epistemologies of popular cultures that are made invisible and denied, as a consequence of the coloniality of power, structure of domination that triggers domination. In view of this, this article proposes to discuss critical interculturality and sociomuseology and their intersections with Freire's praxis. This is a literature review, anchored in research and discussions by Walsh (2009, 2019), Tubino (2016), Moutinho (1993, 2007, 2014), Primo (1999), Freire (1987, 1999, 2005), among others. Both reverberate as decolonizing practices of the hegemonic Eurocentric model, which recognizes a universal epistemology to the detriment of the epistemes of Other cultures, constitute new identity projects of differentiation and have as their horizon the production of other ways of life and knowledge.Keywords: cultures; differentiation; praxis; decoloniality.